Application of ANN control algorithm for optimizing performance of a hybrid ORC power plant - Podlasek, Szymon; Jankowski, Marcin; Bałazy, Patryk; Lalik, Krzysztof; Figaj, Rafał (Energy (Oxford), 2024)
Hybrid systems for generating electricity from multiple sources are becoming an increasingly popular subject of analysis in science and industry. This paper presents a validated model of a hybrid ORC plant powered by solar and geothermal energy. A key challenge in optimizing the operating parameters over time was the variability of solar conditions, which was the main energy source of the system. The operation of the ORC plant is simulated using a complex model with Multiple Input Multiple Output (MIMO) variables, which is nonlinear. The input variables represent the system’s operational parameters, while the output variables describe the plant’s performance indicators. The main objective of this paper is to optimize the year-round performance of the ORC installation through different computational techniques. The first approach involves the application of the gradient-based optimization method that is known as sequential quadratic programming (SQP). With the use of SQP, two distinct simulation runs (SQP-N and SQP-Q/N) of the system are performed, each with a specific objective function to be optimized. The second approach is based on reinforcement learning principles and leverages the method known as Deep Deterministic Policy Gradient (DDPG) algorithm. The main advantage of DDPG over SQP is that DDPG does not require knowledge of the model. This improves the algorithm flexibility, making it well-adapted to fluctuating environmental conditions. Overall, three optimization runs (two using SQP, one using DDPG) have been performed, aiming at identifying the optimal year-round control strategy for the installation. The results revealed that under the control of DDPG, the hybrid system has produced the highest amount of electricity (4993.4 MWh), outperforming in this matter SQP-N and SQP-Q/N optimization variants by 16.83 % and 10.49%, respectively. •Thermodynamic model of a hybrid organic Rankine cycle (ORC) system is developed.•Three approaches for optimizing the annual operation of the ORC are presented.•An approach based on the Deep Deterministic Policy Gradient (DDPG) algorithm is proposed.•Application of the DDPG algorithm results in the best annual performance of the ORC.